2015
DOI: 10.1177/2054270415602828
|View full text |Cite
|
Sign up to set email alerts
|

The psychological effects of reporting extreme violence: a study of Kenyan journalists

Abstract: ObjectiveTo assess the psychological health of journalists in Kenya who have reported on, and been exposed to, extreme violence.DesignDescriptive. Psychological responses were elicited to two stressors, the ethnic violence surrounding the disputed 2007 general election and the Al-Shabab attack on the Westgate Mall in Nairobi.ParticipantsA representative sample of 90 Kenyan journalists was enrolled.SettingNewsrooms of two national news organizations in Kenya.Main outcome measuresSymptoms of post-traumatic stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…This is important not only for mental wellness of the journalism workforce but also for communicating matters of public concern to audiences. Good journalism, according to Feinstein et al (2015), depends on healthy journalists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important not only for mental wellness of the journalism workforce but also for communicating matters of public concern to audiences. Good journalism, according to Feinstein et al (2015), depends on healthy journalists.…”
Section: Discussionmentioning
confidence: 99%
“…Novice reporters who are unsure of how to interview crime victims and unaware of the potential effects of trauma, and thus may be more vulnerable to burnout, guilt, posttraumatic stress disorder (PTSD) symptoms, and unhealthy coping habits (Beam & Spratt, 2009; Dworznik, 2008; Feinstein, Owen, & Blair, 2002). Exposure to trauma reporting strategies and lessons in higher education can foster “trauma-literate” journalists and editors, resulting in a healthier workforce and possibly a more humanized newsroom culture (Amend et al, 2012; Feinstein, Wanga, & Owen, 2015; Massé, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis was undertaken of 8 behavioral datasets of frontline journalists accumulated by one research center between 1999 and 2017. During this period, data were collected from 684 journalists covering the following conflicts: Civil wars in the Balkans ( n = 140) 2 9/11 attack in New York City ( n = 46) 4 2003 Iraq war ( n = 84) 5 Drug conflict in Mexico ( n = 104) 6 Civil war in Syria ( n = 59) 7 Kenya (election violence/Westgate Mall terror attack by Al-Shabab) ( n = 57) 8 Iran (state-sanctioned intimidation ( n = 114) 9 Migration crisis in Europe ( n = 80). 10 We included this group because the refugees were fleeing war zones in Syria and Afghanistan.…”
Section: Methodsmentioning
confidence: 99%
“…Even though media professionals are passionate about their work, the reality of the pandemic causes worries in every stakeholder of their family. Feinstein et al (2014, 2015, 2016), in their field study, found that media professionals working in such a situation suffered post-traumatic stress disorder and anxiety. They revealed that a significant percentage of the population was self-medicating to reduce their stress level and used barbiturates , a sedative typically used to treat insomnia and seizures, which has anti-anxiety effects.…”
Section: Well-being Comfort and Professional Media Lifementioning
confidence: 99%